Fire retardancy of polypropylene/kaolinite composites. (July 2016) - Batistella, Marcos; Otazaghine, Belkacem; Sonnier, Rodolphe; Petter, Carlos; Lopez-Cuesta, Jose-Marie
Abstract: In this study the influence of surface modification of kaolinite with trisilanolisooctyl Polyhedral OligoSilSesquioxane (POSS) in polypropylene composites was evaluated in terms of thermal stability and fire retardancy and compared with talc. Thermogravimetric analysis showed that incorporating 30 wt% of kaolinite enhanced the thermal stability by ca. 20 °C compared to neat polymer. Cone calorimeter results demonstrated that kaolinite can greatly reduce the pHRR but not unmodified kaolinite. Rheological measurements showed that surface treatment of kaolinite leads to a decrease in viscosity, which could enhance processability. Finally, a correlation between viscosity and pHRR was found and the fire behavior of PP containing modified kaolinite could be explained.